Adhesion Molecules: Master Controllers of the Circulatory System. Issue 2 (15th March 2016) - Schmidt, Eric P.; Kuebler, Wolfgang M.; Lee, Warren L.; Downey, Gregory P.
ABSTRACT: This manuscript will review our current understanding of cellular adhesion molecules (CAMs) relevant to the circulatory system, their physiological role in control of vascular homeostasis, innate and adaptive immune responses, and their importance in pathophysiological (disease) processes such as acute lung injury, atherosclerosis, and pulmonary hypertension. This is a complex and rapidly changing area of research that is incompletely understood. By design, we will begin with a brief overview of the structure and classification of the major groups of adhesion molecules and their physiological functions including cellular adhesion and signaling. The role of specific CAMs in the process of platelet aggregation and hemostasis and leukocyte adhesion and transendothelial migration will be reviewed as examples of the complex and cooperative interplay between CAMs during physiological and pathophysiological processes. The role of the endothelial glycocalyx and the glycobiology of this complex system related to inflammatory states such as sepsis will be reviewed. We will then focus on the role of adhesion molecules in the pathogenesis of specific disease processes involving the lungs and cardiovascular system. The potential of targeting adhesion molecules in the treatment of immune and inflammatory diseases will be highlighted in the relevant sections throughout the manuscript. © 2016 American Physiological Society. Compr Physiol 6:945‐973, 2016.